Intervención de enfermería en paciente con preeclampsia, fundamentada en la Teoría de Marjorie Gordon - Cely Calero, Rosicela Paulina; Quinde Luzuriaga, Jennifer Paulette (Machala : Universidad Técnica de Machala, 2022)
Introduction: This document focuses on nursing interventions applied in pregnant patients with a diagnosis of preeclampsia, this multisystem condition is characterized by the presence of arterial hypertension equal to or greater than 140/90 mmHg and proteinuria in pregnant women with a higher gestational age. at 20 weeks, which can cause complications and increase the risk of mortality for the mother and the baby. Preeclampsia currently ranks second in maternal deaths, affecting 2 to 10% of pregnancies worldwide, likewise it mainly affects developing countries. In Latin America, for example, maternal deaths are associated with hypertensive disorders and are responsible for approximately 22.1% of deaths. The care provided by the nursing staff is key to improving the condition of these patients, so it is essential to prioritize the interventions that we are going to carry out in these patients, an adequate follow-up to document the presence of risk factors, signs and symptoms that lead us to a possible diagnosis in addition to severity criteria so as not to reach critical phases. Likewise, it is important that health professionals recognize in a timely manner the risk factors associated with preeclampsia, its complications, proper management and treatment, in order to avoid situations that can cause serious problems in the health of the pregnant woman and of the fetus. It is estimated that approximately 30% of hypertensive disorders during pregnancy are caused by chronic arterial hypertension, while 70% are due to preeclamptic gestational hypertension. Of this last group, 3% are cases of mild preeclampsia.
Introducción: Este documento, se enfoca en las intervenciones de enfermería aplicadas en pacientes embarazadas con diagnostico de preeclampsia, esta afección multisistémica se caracteriza por la presencia de hipertensión arterial igual o superior a 140/90 mmHg y proteinuria en mujeres embarazadas con una edad gestacional superior a las 20 semanas, que puede provocar complicaciones y aumentar el riesgo de mortalidad de la madre y del bebe. Actualmente la preeclampsia ocupa el segundo lugar de muertes maternas afecta del 2 al 10% de los embarazos a nivel mundial, asi mismo afecta principalmente a paises con vias de desarrollo. En America Latina por ejemplo, las muertes maternas se asocian a trastornos hipertensivos y son responsables de aproximadamente el 22,1% de defunciones. La atención que brinda el personal de enfermería es clave para mejorar la condición de estas pacientes, por lo que es esencial priorizar las intervenciones que vamos a realizamos en estas pacientes, un adecuado seguimiento para documentar la presencia de factores de riesgo, signos y síntomas que nos conlleven a un posible diagnostico ademas de creiterios de severidad para no llegar a fases criticas. Asi mismo, es importante que los profesionales de la salud reconozcan de manera oportuna los factores de riesgo asociados con la preeclampsia, sus complicaciones, el manejo y tratamiento adecuado, a fin de evitar situaciones que puedan causar problemas graves en la salud de la gestante y del feto.
Keywords: PREECLAMPSIA, INTERVENCIONES DE ENFERMERIA, TERORIA DE MARJORIE GORDON; PREECLAMPSIA; INTERVENCIONES DE ENFERMERIA; TERORIA DE MARJORIE GORDON